2006
DOI: 10.1128/ec.00380-05
|View full text |Cite
|
Sign up to set email alerts
|

Nature of the Periplastidial Pathway of Starch Synthesis in the CryptophyteGuillardia theta

Abstract: The nature of the periplastidial pathway of starch biosynthesis was investigated with the model cryptophyte Guillardia theta. The storage polysaccharide granules were shown to be composed of both amylose and amylopectin fractions with a chain length distribution and crystalline organization very similar to those of starch from green algae and land plants. Most starch granules displayed a shape consistent with biosynthesis occurring around the pyrenoid through the rhodoplast membranes. A protein with significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 37 publications
2
38
0
1
Order By: Relevance
“…This may imply that starch granule aggregation could dispense with the postulated debranching mechanism, although the crystallinity of this residual material still needs to be ascertained. Second, some of the secondary endosymbiosis lineages derived from Archaeplastida, as well as some little studied semiamylopectin accumulating cyanobacteria, were reported to lack candidate-direct DBE genes (Deschamps et al, 2006;Ball et al, 2011;Colleoni and Suzuki, 2012;Curtis et al, 2012). This observation would imply a nonessential function of polysaccharide debranching in amylopectin synthesis.…”
Section: Evolution Of Direct Dbes Involved In Amylopectin Maturation mentioning
confidence: 94%
See 2 more Smart Citations
“…This may imply that starch granule aggregation could dispense with the postulated debranching mechanism, although the crystallinity of this residual material still needs to be ascertained. Second, some of the secondary endosymbiosis lineages derived from Archaeplastida, as well as some little studied semiamylopectin accumulating cyanobacteria, were reported to lack candidate-direct DBE genes (Deschamps et al, 2006;Ball et al, 2011;Colleoni and Suzuki, 2012;Curtis et al, 2012). This observation would imply a nonessential function of polysaccharide debranching in amylopectin synthesis.…”
Section: Evolution Of Direct Dbes Involved In Amylopectin Maturation mentioning
confidence: 94%
“…Until recently, the distribution of starch seemed restricted to photosynthetic eukaryotes, including several secondary endosymbiosis lineages derived from Archaeplastida, such as the cryptophytes (Deschamps et al, 2006), the dinoflagellates (Dauvillée et al, 2009), and some apicomplexa parasites (Coppin et al, 2005). However, more recent studies revealed the existence of starch-like structures in unicellular diazotrophic cyanobacteria belonging to the order Chroococcales (Nakamura et al, 2005;Deschamps et al, 2008;Suzuki et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…2.4.5) reveals many PPC-localized reactions catalysed by key enzymes such as glucan, water dikinase, alpha-amylase, hexokinase, 6-phosphofructokinase and phosphoglucomutase. These enzymes form a link to the synthesis and degradation of starch, which occurs in the PPC in G. theta 25 . Thirty-six candidate proteins for PPC, plastid or cytosol metabolite shuttling …”
Section: Research Articlementioning
confidence: 99%
“…Initially, this enzyme was considered to be the main starch synthesizing activity (Hanes, 1940). Later, both starch and glycogen synthases have been discovered that utilize either ADPglucose or UDPglucose (or both; Deschamps et al, 2006) as hexosyl donor. Ample evidence has been presented that these enzymes are essential biosynthetic enzymes (Ballicora et al, 2003;Zeeman et al, 2010;Roach et al, 2012;Palm et al, 2013).…”
mentioning
confidence: 99%